Effect of surfactants on the improved selectivity and anti‐bacterial efficacy of citronellal nano‐emulsion. (8th October 2018) - Guliani, Anika; Singla, Rubbel; Kumari, Avnesh; Acharya, Amitabha
Abstract: Essential oils, the so‐called "green pesticides, " possess strong anti‐microbial activities due to their characteristic aroma; but low efficacy, instability, and high cost of production, mostly restrict their use in food and pharma industry. In this context, citronellal nano‐emulsification process was optimized using different concentrations of Brij‐58 and leaf extracts of Lantana camara . Results suggested that uniform droplet size of 35–70 nm can be achieved when CL concentration was maintained at 2% (v/v). Efficacy of both the prepared nano‐emulsions was tested against two different strains of bacteria viz., Staphylococcus aureus and Pseudomonas aeruginosa using TEM and confocal microscopic techniques. Studies indicated an early and selective killing of both the bacteria by citronellal nano‐emulsion as compared to pure citronellal. It is being proposed that noncovalent interactions and presence of aquaporins on the bacterial membrane were largely responsible for such selectivity. Practical applications: The demand for natural anti‐microbial compounds has been increasing in the food industry to reduce the food‐borne pathogens and also to minimize the use of synthetic anti‐microbial compounds. Due to their strong aroma, essential oils are primarily used in perfumes, soaps, foods, flavors, and beverages as well as in anti‐microbial activities which can be used as food preservatives and cosmeceuticals to extend the shelf‐life of such products. However, the use of essential oils is limited, as these possess certain disadvantages of being highly volatile, expensive, and less effective at a certain minimum concentration, etc. The present study is based on the optimization of the nano‐emulsification process for the citronellal, by using chemical and green surfactants. The anti‐bacterial activities have been tested against two bacterial strains, Staphylococcus aureus and Pseudomonas aeruginosa . The anti‐bacterial studies carried out using TEM and confocal microscopy suggested that the nano‐emulsion containing citronellal caused an early and selective killing of bacteria compared to the pure citronellal.